Vision and Mission: To Restore and Work on a Narrative About South Africa and the Netherlands for Our (Grand)Children and Future Generations - Sens, Angelie; Steinmetz, Carl H. D.; Hoek, Anneke; Lafour, Gina (Advances in Social Sciences Research Journal, 2024)
This article shows a contrast between the morality of South Africa and the Netherlands. The latest example is the courtcase before the International Court of Justice in The Hague. The Netherlands is conspicuously keeping its distance. This may be explained by the neo-colonial attitude of the Netherlands during the period when it colonised, enslaved, looted and pillaged South Africa, imposed indentured labour and established apartheid. This article attempts to initiate a new narrative that transcends this sickening history, a narrative intended for South African and Dutch great-grandchildren. We see this narrative as a start for rewriting history, but also for writing children's books and creating restorative art expressions.